PENGARUH RASIO RETURN ON ASSET, EARNING PER SHARE DAN DEBT TO EQUITY RATIO TERHADAP HARGA SAHAM PADA PERUSAHAAN F&B TERDAFTAR DI BEI - Fatricia, Vinola Aura; Fachruddin, Wan; Dwilita, Handriyani (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2025)
The purpose of this study is to examine the impact of return on assets, earnings per share and debt-to-equity ratios on the stock prices of F&B companies listed on the IDX during 2019-2022. The population in this study was F&B companies listed on the IDX, with a total sample of 25 companies. The sampling technique used in this study was purposive sampling. The research method used is associative with data sources in the form of secondary data. The data analysis technique used is statistical data processing. The results of this study indicate that the independent variables, namely ROA, EPS and DER ratios, simultaneously have a significant impact on the share prices of F&B companies listed on the IDX during the period 2019-2022.